Priorities for peri‐operative research in Africa. (5th January 2020) - Biccard, B.M.; ,
Summary: Deaths following surgery are the third largest contributor to deaths globally, and in Africa are twice the global average. There is a need for a peri‐operative research agenda to ensure co‐ordinated, collaborative research efforts across Africa in order to decrease peri‐operative mortality. The objective was to determine the top 10 research priorities for peri‐operative research in Africa. A Delphi technique was used to establish consensus on the top research priorities. The top 10 research priorities identified were (1) Develop training standards for peri‐operative healthcare providers (surgical, anaesthesia and nursing) in Africa; (2) Develop minimum provision of care standards for peri‐operative healthcare providers (surgical, anaesthesia and nursing) in Africa; (3) Early identification and management of mothers at risk from peripartum haemorrhage in the peri‐operative period; (4) The role of communication and teamwork between surgical, anaesthetic, nursing and other teams involved in peri‐operative care; (5) A facility audit/African World Health Organization situational analysis tool audit to assess emergency and essential surgical care, which includes anaesthetic equipment available and level of training and knowledge of peri‐operative healthcare providers (surgeons, anaesthetists and nurses); (6) Establishing evidence‐based practice guidelines for peri‐operative physicians in Africa; (7) Economic analysis of strategies to finance access to surgery in Africa; (8) Establishment of a minimum dataset surgical registry; (9) A quality improvement programme to improve implementation of the surgical safety checklist; and (10) Peri‐operative outcomes associated with emergency surgery. These peri‐operative research priorities provide the structure for an intermediate‐term research agenda to improve peri‐operative outcomes across Africa.